MITIGATING AMMONIA VOLATILIZATION LOSSES USING BIOCHAR AMENDMENTS IN AN UPLAND RICE SOIL IN YOLA, ADAMAWA STATE, NIGERIA - Solomon, Rejoice Ibrahim; Saddiq, Abdillahi Muhammad; Musa, Salihu Ardo; Dauna, Yakubu; Nubiya, Peace (FUDMA Journal of Sciences, 2026)
Ammonia volatilization is a primary way of nitrogen (N) loss in tropical agriculture, particularly in neutral or alkaline soils. This study evaluated the potential of maize cob biochar (MCB), rice husk biochar (RHB), and locally sourced conventional charcoal (CCB) for reducing NH3 loss in moist and submerged soils. MCB and RHB were pyrolyzed at 450°C while CCB was sourced locally and applied at rates of 0–20 ton ha⁻¹ to urea-treated soils. The experiment was layout in two-factor completely randomized design. Volatilization was monitored over 21 days in closed chambers under two moisture regimes: 80% available water capacity (moist) and 2 cm standing water. Results revealed that in moist soils, high application rates (20 ton ha⁻¹ MCB) significantly increased NH3 loss to 0.64 g kg⁻¹ due to elevated soil pH, while low rate CCB (5 ton ha⁻¹) matched the control (0.37 g kg⁻¹). Cumulative losses in moist conditions ranged from 2.21 to 3.5 g kg⁻¹ with no consistent reduction across biochar rates. However, in submerged soils, the control exhibited the highest cumulative losses (4.36 g kg⁻¹). Application of 5 ton ha⁻¹ CCB reduced volatilization by 46 %, likely through O-H adsorption and CO2-carbonic acid buffering. While losses peaked between 10 and 14 days across both regimes, high-pH porous biochars often increased volatilization in moist soils. The study concludes that 5 ton ha⁻¹ of CCB is a practical, low-cost strategy for reducing N loss in flooded savanna systems. Effective N management remains highly dependent on feedstock type and soil moisture conditions.
Keywords: Ammonia volatilization; biochar; conventional charcoal; Nigerian savanna; nitrogen use efficiency